2013
DOI: 10.1097/fjc.0b013e318279b7b1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAPK During Ischemia, But Not Reperfusion, Effectively Attenuates Fatal Arrhythmia in Ischemia/Reperfusion Heart

Abstract: The mitogen-activated protein kinases (MAPKs) play an important role in ischemia/reperfusion (I/R) injury. Previous evidence suggests that p38 MAPK inhibition before ischemia is cardioprotective. However, whether p38 MAPK inhibition during ischemia or reperfusion provides cardioprotection is not well known. We tested the hypothesis that p38 MAPK inhibition at different times during I/R protects the heart from arrhythmias, reduces the infarct size, and attenuates ventricular dysfunction. Adult Wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 46 publications
4
67
0
Order By: Relevance
“…These findings suggest that p53 and CREB are downstream molecules of p38 MAPK that were not activated via HSP27, or could possibly be regulated by other unidentified signaling pathways that could be affected by SB203580. Furthermore, SB203580 given at reperfusion could only reduce cleaved caspase 3 levels without any change in the Bax, Bcl2, and cytochrome c. The reduction of cleaved caspase 3 level could sufficiently attenuate the apoptotic pathway, which is consistent with the results from our previous report that SB203580 given at the onset of reperfusion also reduced the infarct size (Surinkaew et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that p53 and CREB are downstream molecules of p38 MAPK that were not activated via HSP27, or could possibly be regulated by other unidentified signaling pathways that could be affected by SB203580. Furthermore, SB203580 given at reperfusion could only reduce cleaved caspase 3 levels without any change in the Bax, Bcl2, and cytochrome c. The reduction of cleaved caspase 3 level could sufficiently attenuate the apoptotic pathway, which is consistent with the results from our previous report that SB203580 given at the onset of reperfusion also reduced the infarct size (Surinkaew et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…However, giving SB203580 at the onset of reperfusion failed to prevent the loss of mitochondrial membrane potential, in which cardiac mitochondrial depolarization plays an important role in arrhythmogenesis (O'Rouke, 2000). These findings could provide the mechanistic explanation of our previous report, which demonstrated from our previous study that the infarct size reduction was found at all-time points of SB203580 treatment, but treatment of SB203580 before or during ischemia, but not at reperfusion, decreased the incidence of ventricular tachycardia/ventricular fibrillation (VT/VF) incidence (Surinkaew et al, 2013). Although SB203580 showed a protective effect on cardiac mitochondrial swelling, ROS production, and mitochondrial membrane potential depolarization, the mitochondrial respiration was not performed and was considered a limitation of this study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Left ventricular tissues were lysed with extraction buffer (20 mmol l −1 Tris-HCl, 1 mmol l −1 Na 3 VO 4 and 5 mmol l −1 NaF), separated by electrophoresis on 10% sodium dodecyl sulfatepolyacrylamide gel and transferred onto nitrocellulose membranes (Surinkaew et al 2013). Immunoblots were blocked for 1 h with 5% non-fat dry milk in Tris-buffered saline (pH 7.4) containing 0.1% Tween 20.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…This adverse effect has been shown to be even more severe in obese insulin resistance, resulting in increased infarct size and increased myocardial susceptibility to ischemia-reperfusion (I/R) injury [3], [4]. I/R injury has been shown to associate with fatal cardiac arrhythmias [5]. Cardiac mitochondrial damage has been implicated as one of the major factors responsible for myocardial cell death from I/R injury [6].…”
Section: Introductionmentioning
confidence: 99%